Phenotypic ASCOD characterisations of ischaemic stroke in the young at an urban tertiary care centre. Issue 4 (30th July 2018) - Liu, Angela; Pirastehfar, Mohsen; Yu, Daohai; Linares, Guillermo
Abstract : Background and purpose: Stroke in young individuals is a serious public health burden. This study aimed to characterise the various phenotypes of ischaemic stroke in a young urban population (≤50 years old) using the ASCOD classification system, which assigns a score to five stroke categories: atherosclerosis, small vessel disease (SVD), cardioembolism, other and dissection. Within each category, a numerical score represents the degree of causality attributed to the stroke. Methods: This retrospective study cohort was composed of patients from an urban tertiary care academic centre. Cases were selected by searching Get With the Guidelines database for adults ≤50 years old with ischaemic stroke. The study sample included 175 ischaemic strokes in 157 patients, with 16 subjects re-infarcting. Using retrospective chart review, each stroke was scored according to the ASCOD classification system. Multivariable logistic regression analyses were performed to explore each ASCOD category's association with causal risk factors. Results: Of possible causal mechanisms, defined as receiving a grade 1 or 2, a cardiovascular aetiology was most prevalent (25.7%), followed by SVD (22.3%), and closely by atherosclerosis (21.1%). Of general phenotypes, defined as receiving a grade 1 or 2 or 3, atherosclerosis was the most prevalent (51.4%), followed by SVD (47.4%), cardioembolism (42.3%) and other (35.4%). 31.6% of all strokes were of unclear aetiology. Subjects between 45 and 50 years old were more likely to develop a cardioembolic or SVD stroke when compared with subjects <45 years old. Conclusion: This study took a novel approach to ASCOD phenotyping, allowing several observations: (1) In patients with advanced atherosclerosis receiving the score A1, the vast majority had systemic atherosclerosis in multiple vascular territories; (2) the cardiac score C2(6), defined as a radiographic pattern highly suggestive of a central embolic source, may overestimate the prevalence of true cardiac disease; (3) incidental laboratory findings may detect some underlying pathology, but causality to the stroke is unlikely.